Cyanide Prevents the Inhibition of Platelet Aggregation by Nitroprusside, Hydroxylamine and Azide - Schwerin, Francis T; Rosenstein, Robert; Smith, Roger P (Thrombosis and Haemostasis, 1983)
Sodium cyanide (CN-) in concentrations of 10 uM or more prevented the inhibition of epinephrine (2.5 uM) and of ADP (4.0 uM) induced primary and secondary aggregation brought about by 10 uM sodium nitroprusside (SNP). Cyanide alone in the same concentration had no effect on platelet aggregation induced by epinephrine or ADP. Even when the addition of CN- was delayed for as long as 9 min after epinephrine and SNP, it immediately reversed the SNP block and initiated a bimodal wave of aggregation. The effect of CN- on SNP inhibition of platelet aggregation appears to be competitive and reversible. Although they are less potent inhibitors of platelet aggregation than SNP, the effects of hydroxylamine (HA) and azide were also prevented by SNP. In our hands, sodium nitrite did not inhibit platelet aggregation consistently. The inhibitory effects of glyceryl trinitrate, papaverine and nitric oxide hemoglobin on platelet aggregation were not prevented by CN-. These interactions probably have no significance in vivo, but they indicate that SNP, HA and azide act on platelets and on vascular smooth muscle by similar or identical biochemical mechanisms. They also suggest that there are at least two sub-classes of so-called nitric oxide vasodilators. The effect of CN- may be mediated through an inhibition of the formation of nitric oxide from SNP, HA and azide.
Keywords: Platelets; Nitroprusside; Cyanide; Hydroxylamine; Azide; Nitric oxide